REDESAIN STRUKTUR BANGUNAN JETTY DI MUARA AIR PALIK, KECAMATAN AIR NAPAL, BENGKULU UTARA - Syafrizal Budi Artha; Besperi Besperi; Muhammad Fauzi (Universitas Bengkulu, 2019)
This research discusses the evaluation of the high waves, water level and redesign the dimension of jetty by replacing the protective layer of artificial stones made from concrete (quadripot). The data used in this study is from BMKG (Meteorology, Climatology and Geophysics Stasiun) Class 1 Pulau Baii Bengkulu which is the maximum wind data for the last 10 years (2005 - 2014) and tide data for the last 5 years (2007, 2008, 2009, 2012, and 2013). The primary data is the data of wave height conducted at the site for 14 days . The results of calculation from BMKG and data recording from the site, the highest wave break obtained is from the calculation from BMKG which is 3.34 meters and 8.13 second wave period. The results obtained from the analysis of jetty is HWL = 1.50 meters, MWL = 1.08 meters, LWL = 0.10 meters, DWL = 2.50 meters, peak elevation of the building = 5.1 meters , building height = 9,1 meter, protection layers of the head section weight = 1.2 tons, weight of the protection layers of the sleeve section 2.7 tons, thickness of protection layer of head section = 2 meters, thickness of protection layer of sleeve section = 2.5 meters, widht of protection layer of head section = 2.5 meters , width of protection layer of sleeve section = 3.5 m , the number of grains per unit area ( N ) in protection layer in head section = 17 grains per 10 m2 , and the number of grains per unit area ( N ) in protection layer in sleeve section = 10 grains per 10 m2 .